Developments in the "LNG to Power" market and the growing importance of floating facilities - Mike Wyllie (The Oxford Institute for Energy Studies, 2021)
Land-based LNG import terminals were introduced in the 1960s to import LNG from the first liquefaction plants in Algeria and the USA and dispatch gas into national distribution grids. Since then, some 150 LNG import terminals have been built around the world. In the last 20 years there has been a growth in the number of floating LNG import terminals facilities which have become popular since they can generally be deployed more quickly and at a lower cost than onshore facilities. This paper looks at this trend of LNG import terminals moving from land-based to floating installations and discusses the emerging trend of floating power plants. Leased power barges and power ships are now available on the market up to 500 MW, and in the future, this could grow to 1 GW capacity. The discussion examines five different LNG to Power schemes and makes a detailed technical and commercial comparison of two of these - the FSRU plus FPP (Floating Power Plant) as two separate vessels, and the FSRP vessel (Floating Storage, Regasification and Power Generation) where the same functionality is integrated into a single unit. The technical pros and cons of each option are discussed, and the LCOEs calculated for a Reference Case to also draw commercial conclusions. In terms of overall demand, anticipated growth in the floating 'LNG to Power' market is expected to be around one to two GW per year of installed capacity over the next five years, with these new projects mainly located in South America, West Africa and South-East Asia. This would add new LNG demand each year of around one to two mtpa.
Keywords: 330; floating LNG; Floating Power Generation; FSRU; LNG; Power